Practice of Electromagnetic Contactor Coil Working Status - GENG Xin; LIU Yue-ming (机车电传动)
Taking CX1015/08 LB electromagnetic contactor utilized in CRH3 EMUs as study object, a new method for judging contactoroperating mechanism failure by checking and comparing the coil current curves was proposed, which could quantify the failure status byanalyzing coil current waveform. Probability of the method was confirmed by test results, a test system design scheme was provided for realtimemonitoring the working status of the electromagnetic contactor.